Jane Eyre (1997) [videorecording (DVD)] - Young, Robert, 1933-; Hinds, Ciarán, 1953-; Morton, Samantha; Jones, Gemma; Brontë, Charlotte, 1816-1855 (A & E Home Video, 1999)
Jane Eyre, a mistreated orphan, learns to survive by relying on her independence and intelligence.